Audit fees and earnings management: differences based on the type of audit. Issue 1 (1st January 2021) - Gandía, Juan L.; Huguet, David
Abstract: In spite of the extensive research about the impact of audit fees on audit quality, there is no research examining if the association between voluntary audits and audit pricing affects audit quality. Therefore, the aim of this paper is to empirically examine whether the effect of audit fees on audit quality, measured by the level of earnings management, is affected by the type of audit (voluntary vs mandatory), as well as whether the effect of audit fees on audit quality is different depending on the type of audit. Using a sample of Spanish SMEs composed of both voluntarily and mandatorily audited companies, we find that voluntary audits have higher quality when audit fees are lower, but the differences in audit quality between voluntary and mandatory audits reverse as audit fees increase, and mandatory audits are more effective at deterring earnings management when audit fees are high. Additional analyses show that voluntary audits do not directly affect earnings management; instead, voluntary audits are associated with abnormal fees, which in turn negatively affect earnings management. The results also show that audit fees are only negatively associated with earnings management when accruals are income-increasing, which is related to auditor conservatism.